Implementasi Costumer Relationship Management (CRM) Pada Sistem Informasi Penjualan Ban Di Toko Lingga Ban Berbasis Web - Ipan Supandi; Fahmi Yusuf; Fauziah F (NUANSA INFORMATIKA, 2018)
The store Lingga Tires is a trademark unit engaged in the sale of the tires. The store Lingga Tires only rely on the conventional sales namely the subscriber must come into the store and doing transaction at the store. This makes the customer became less know the products in the market and the existing promotion. The store Lingga Tires want to provide a satisfactory services with want to deliver innovation and convenience for customers. To store the Lingga Tires need a means to support the sales transaction and media promotions effective means of implementing the method Customer Relationship Management (CRM) web-based. CRM is one of the means to build a good relationship with customers and to acquire new customers. Web-based Sales information system is built by the method of software development waterfall , the language of PHP programming technique, MySQL database as data storage and testing method using the black box white box testing this system can be used by the administrator, customers and direction. The administrator is the person who manages the whole system. Customers can make your reservation, payment confirmation and have points shopping. The direction of instructions view report, this system is expected to be a solution to overcome the problems and to be able to increase sales in the Store Lingga Tires.Key Words: Information System,Sale,CRM, Web, Store Lingga Tires